CLINICO-HAEMATOLOGICAL STUDIES ON CLINICAL MASTITIS IN GOATS IN AND AROUND HYDERABAD - D. SREE PRIYA,; S. AYODHYA, (International Journal of Pharma and Bio Sciences, 2016)
The present study was carried out to study the clinical and haematological changes in goats affected with clinical mastitis during the period June, 2013 to May, 2014. Affected goats showed inflammatory signs like swelling, erythema, warmth, hardness, pain in the udder, reduced milk production and systemic involvement in the form of fever, depression, anaemia and weakness. The estimation of haematological parameters revealed a significant (p≤0.01) decrease in haemoglobin, packed cell volume, total leucocyte count in mastitic goats. Leucogram revealed lymphocytosis, eosinophilia, monocytosis and neutropenia.